Managing the Impact of Climate on Migration: Evidence from Mexico - Isabelle Chort; Maëlys de la Rupelle (Global Labor Organization (GLO), 2022)
While there is a growing literature on the impact of climate and weather-related events on migration, little is known about the mitigating effect of different policies directed to the agricultural sector, or aimed at insuring against environmental disasters. This paper uses state-level data on migration ows between Mexico and the U.S. from 1999 to 2012 to investigate the mitigating impact of an agricultural cashtransfer program (PROCAMPO) and a disaster fund (Fonden) on the migration response to weather shocks. We find that Fonden decreases migration in response to heavy rainfall, hurricanes and droughts. Increases in PROCAMPO amounts paid to small producers are found to play a more ambiguous role on the migration response to shocks. Changes in the distribution of PROCAMPO favoring more vulnerable producers in the non irrigated ejido sector however seem to mitigate the impact of droughts on migration.
Keywords: F22; Q54; Q18; O15; J61; 330; International migration; Weather shocks; Public policies; Weather variability; Natural disasters; Mexico-U.S. migration; Inequality